2018
DOI: 10.1007/978-3-319-97427-9_12
|View full text |Cite|
|
Sign up to set email alerts
|

The Genetics and Genomics of Virus Resistance in Maize

Abstract: Viruses cause significant diseases on maize worldwide. Intensive agronomic practices, changes in vector distribution, and the introduction of vectors and viruses into new areas can result in emerging disease problems. Because deployment of resistant hybrids and cultivars is considered to be both economically viable and environmentally sustainable, genes and quantitative trait loci for most economically important virus diseases have been identified. Examination of multiple studies indicates the importance of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 111 publications
(143 reference statements)
0
16
0
1
Order By: Relevance
“…In adition, this cluster reported in bin 2.02 contains a major QTL resistant to Mal de Río Cuarto virus and/or Maize Rough Dwarf virus, which was patented by Martin et al (2010). On chromosome 6, Redinbaugh et al (2018) reported overlapping of loci conferring resistance to different viruses at 157 Mb. In a very close position, we identified a significant common genomic region for both traits and Rossi et al (2015) reported a QTL for SEV of MRC identified in a F 2:3 population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In adition, this cluster reported in bin 2.02 contains a major QTL resistant to Mal de Río Cuarto virus and/or Maize Rough Dwarf virus, which was patented by Martin et al (2010). On chromosome 6, Redinbaugh et al (2018) reported overlapping of loci conferring resistance to different viruses at 157 Mb. In a very close position, we identified a significant common genomic region for both traits and Rossi et al (2015) reported a QTL for SEV of MRC identified in a F 2:3 population.…”
Section: Discussionmentioning
confidence: 99%
“…Genes and genomic regions conferring resistance to various pathogens often reside in clusters (McMullen & Simcox 1995; Redinbaugh, Lübberstedt, Leng, & Xu, 2018). On bin 2.02, where a genomic region linked to both INC and SEV of MRC was mapped, three loci conferring resistance to three different viral diseases were previously identified (Dintinger et al., 2005; Jones et al., 2018; Luan, Wang, Li, Zhang, & Zhang, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using GWAS, we identified one region in bin 2.02 for DSI‐MRC that coincides with previously reported virus resistance QTL. Redinbaugh, Lübberstedt, Leng, and Xu (2018) reported QTL cluster for virus‐borne diseases in this bin. Specifically, the cluster reported in bin 2.02 contains a major QTL resistant to Mal de Rio Cuarto virus or Maize Rough Dwarf virus , which was patented by Martin et al.…”
Section: Discussionmentioning
confidence: 75%
“…En el mismo bin, en nuestro trabajo identificamos un SNP asociado al ISE de la enfermedad. Redinbaugh et al (2018) combinaron resultados de estudios donde se identificaban QTL para resistencia a enfermedades virales en maíz e identificaron nueve regiones del genoma donde se agrupaban loci de resistencia (clusters). Uno de esos clusters se ubica en el bin 2.08 y reporta QTL de resistencia para tres enfermedades virales.…”
Section: I S C U S I ó Nunclassified